On exact solutions for the stochastic time fractional Gardner equation - Körpınar, Zeliha; Tchier, Fairouz; İnç, Mustafa; Alorini, Ayesha Abdulrahman (Iop Publishing Ltd, 2020)
In this work, the stochastic time fractional Gardner equation is analysed. Some white noise functional solutions for this equation are obtained by using white noise analysis, Hermite transforms and the modified fractional sub-equation method. These solutions include exact stochastic trigonometric functions, hyperbolic functions solutions and wave solutions.
Inc, Mustafa/0000-0003-4996-8373
Keywords: the stochastic time fractional Gardner equation; Hermite transforms; the modified fractional sub-equation method